A 10-amino-acid sequence in the N-terminal A/B domain of thyroid hormone receptor alpha is essential for transcriptional activation and interaction with the general transcription factor TFIIB. - Hadzic, E (1995)
The effects of the thyroid hormone (3,5,3'-triiodo-L-thyronine [T3]) on gene transcription are mediated by nuclear T3 receptors (T3Rs). alpha- and beta-isoform T3Rs (T3R alpha and -beta) are expressed from different genes and are members of a superfamily of ligand-dependent transcription factors that also includes the receptors for steroid hormones, vitamin D, and retinoids. Although T3 activates transcription by mediating a conformational change in the C-terminal approximately 220-amino-acid ligand-binding domain (LBD), the fundamental mechanisms of T3R-mediated transcriptional activation remain to be determined. We found that deletion of the 50-amino-acid N-terminal A/B domain of chicken T3R alpha (cT3R alpha) decreases T3-dependent stimulation of genes regulated by native thyroid hormone response elements about 10- to 20-fold. The requirement of the A/B region for transcriptional activation was mapped to amino acids 21 to 30, which contain a cluster of five basic amino acids. The A/B region of cT3R alpha is not required for T3 binding or for DNA binding of the receptor as a heterodimer with retinoid X receptor. In vitro binding studies indicate that the N-terminal region of cT3R alpha interacts efficiently with TFIIB and that this interaction requires amino acids 21 to 30 of the A/B region. In contrast, the LBD interacts poorly with TFIIB. The region of TFIIB primarily involved in the binding of cT3R alpha includes an amphipathic alpha helix contained within residues 178 to 201. Analysis using a fusion protein containing the DNA-binding domain of GAL4 and the entire A/B region of cT3R alpha suggests that this region does not contain an intrinsic activation domain. These and other studies indicate that cT3R alpha mediates at least some of its effects through TFIIB in vivo and that the N-terminal region of DNA-bound cT3R alpha acts to recruit and/or stabilize the binding of TFIIB to the transcription complex. T3 stimulation could then result from ligand-mediated changes in the LBD which may lead to the interaction of other factors with cT3R alpha, TFIIB, and/or other components involved in the initiation of transcription.